Concise enantioselective synthesis of 1,4-dideoxy-1,4-imino-D-arabinitol using Co(III)(salen)-catalyzed hydrolytic kinetic resolution of a two-stereocentered anti-azido epoxide - Reddi, Rambabu N.; Prasad, Pragati K.; Kalshetti, Rupali G.; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2017)
A concise enantioselective synthesis of 1,4-dideoxy-1,4-imino-D-arabinitol, (+)-DAB-1, has been described in good overall yield (18.1%) and with high enantiomeric purity (up to 98% ee) starting from a simple raw material, cis-2-butene-1,4-diol. The Co-catalyzed hydrolytic kinetic resolution of a two-stereocentered racemic azido epoxide followed by asymmetric dihydroxylation of the alkene and 'one pot' reductive cyclisation of the azido diol are key reactions in the synthetic sequence. (C) 2016 Elsevier Ltd. All rights reserved.